Síndrome metabólica em funcionários de uma universidade pública: fatores associados e concordância entre critérios de diagnósticos - Ana Luisa Marcucci Leão (2013)
The Metabolic syndrome (MetS) is independently associated with type 2 diabetes mellitus and cardiovascular diseases. Actually, work condition is recognized as a possible risk factor of chronic diseases. The main objective of this study was to analyze the factors associated with MetS and the concordance between diagnosis criteria among health campus employees of a public university. Epidemiological, cross-sectional and analytical study, with 211 health campus employees of a public health in Belo Horizonte city, Minas Gerais State, Brazil. We applied a questionnaire with demographic, socioeconomic, anthropometric and life style variables. MetS was defined according to criteria proposed by NCEP-ATP III, IDF and AHA/NHBLI. Statistical analyses were descriptive (absolutes and relatives frequencies), bivariate (Persons chi-square and Fisher exact tests) and multivariate (Poisson regression), with significance level of 5% (p < 0.05). Concordance of MetS definitions was evaluated with Kappa test. MetS prevalences were 27% (95% CI: 21.1-33.5) NCEP, 33.2% (95% CI: 26.9-40.0) IDF and 28.4% (95% CI: 22.5-35.0) AHA/NHLBI. Overweight and obesity were independently associated with MetS to all diagnosis criteria. Furthermore, income 6 minimum wages (PR = 0.52; 95% CI = 0.29-0.95) NCEP, high social support (PR = 1.55; 95% CI = 1.08-2.21) IDF and age (PR = 1.02; 95% CI = 1.00-1.04) NHLBI/AHA also were independently associated with MetS. The percentages of concordance between the diagnosis criteria were high (> 85%). Using the Kappa test, NCEP and AHA/NHLBI were the diagnosis criteria most concordant (0.965; p < 0.001). MetS prevalence was high and it should be considerate in discussions on worker health promotion. Results demonstrated the necessity of consensual MetS diagnosis criteria.